Comparison of CPAP with Humidifie, Blender, and T-piece on the Outcome of Weaning in Patients with Neurological Disorders - BILAN, Nemat; GANJI, Shalaleh (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Bilan N, Ganji Sh. Comparison of CPAP with Humidifie, Blender, and T-piece on the Outcome of Weaning in Patients with Neurological Disorders. Iran J Child Neurol. Spring 2015;9(2):42-45. Abstract Objective The procedure for weaning from mechanical ventilation in many patients is a difficult and long process and increases the time of mechanical ventilation. There are numerous ways to achieve weaning. One common method is the use of CPAP. Considering the lower price of a humidifier, blender, and T-piece compared with CPAP and in light of the limited number of studies in this field the current study purposed to compare these two procedures. Materials & Methods Fifty-one patients with neurological disorders who were under mechanical ventilation and ready to wean were allocated randomly into two groups: the CPAP group and the humidifier, blender, and T-piece group. Duration of hospital and PICU stay, number of days under mechanical ventilation, frequency of re-intubation, and mortality rate among patients were documented. Results The patients were 33 males and 18 females (64.7% and 35.3%, respectively) with an average age of 22.5 ± 4.5 months. The main indication for intubation was impending respiratory failure. Hospital stay was 22±15 and 21±13 days for the humidifier and CPAP groups, respectively. PICU stay was 13±11 and 21±13 days for the humidifier and CPAP groups, respectively. Re-intubation rates were 17.2% and 45.5% for the humidifier and CPAP groups, respectively. Mortality rates were 3.4% and 22.5% for the humidifier and CPAP groups, respectively. Conclusion Considering no statistically significant difference between the two groups, using the humidifier, blender, and T-piece is recommended.